Effect of alumina fiber content on pore structure and properties of porous ceramics. Issue 2 (16th October 2018) - Lang, Ying; Zhao, Lin; Dai, Xin; Wang, Chang‐An
Abstract: Porous Al2 O3 ceramics with different contents of alumina fibers were prepared by gel‐casting process. The effects of Al2 O3 fiber content on pore size distribution, porosity, compressive strength, and load‐displacement behavior of the ceramic materials were investigated. Initial results showed that with the increase of Al2 O3 fiber content, the pore size and porosity of the material is increased, and the compressive strength is decreased. However, upon increasing the fiber content from 50 wt% to 67 wt%, the performance of the samples changed greatly. The compressive strength of the material increased, while the porosity remained unchanged, the pore size increased greatly, and the shape of the load displacement curve changed. It showed that when the fiber content increased from 50 wt% to 67 wt%, the loading body in the fiber‐reinforced porous ceramics changed from particles to fibers.